EVALUATION AND REDESIGN USER INTERFACE METOOCEL APPLICATION USING HUMAN CENTERED DESIGN METHOD - Muhammad Shalahuddin Aldi Baihaqi; Indra Lukmana Sardi; Rosa Reska Riskiana (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
Metoocel application is the name of the application from a shop that sells smartphone and laptop accessories in the Surabaya area. Metoocel application was created to make it easier for users to view product catalogs and make product purchases online through the application without the need to come to the location. However, Metoocel application has never been evaluated regarding usability since the application was created. Therefore, it is necessary to evaluate to determine the usability value of the Metoocel application. Through the initial evaluation of the study using the System Usability Scale questionnaire, the Metoocel application obtained a score of 54 so that it was included in the "F" grade scale category and the "Low Marginal" acceptability ranges category. This shows that Metoocel application still has shortcomings related to application usability. To overcome these problems, a redesign of the user interface was carried out using the Human Centered Design method which focused on user needs in Metoocel application. The result of the redesign is a prototype of Metoocel application. Then, the prototype that has been designed is evaluated using SUS to compare the usability value of the application before and after redesigning the user interface. The test results show that the prototype gets a score of 80 including the grade scale category "B" and the Acceptability Ranges category "Acceptable" which means the function of the application prototype has worked well and can increase the usability value of the application.